Eyematch: An Eye Localization Method for Frontal Face Images - Colak, Muhammed Emre; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2019)
In this paper, a novel approach to detect iris from images which contains frontal faces is proposed. The approach can be used for real time eye detection from cheap web cameras or other kind of cameras. First face region is detected by using haar cascades for frontal faces than possible eye region chosen from the face region. The eye regions reduced with the foreknowledge which is eyes are darker. Reduced image used with a tailored template matching algorithm to determine where eye really is. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: eye detection; eye localization; template matching